Pengaruh Disiplin Kerja dan Lingkungan Kerja Fisik Terhadap Produktivitas Pegawai Pada Dinas Koperasi, Perindustrian dan Perdagangan Kota Bima - Uswatul Hasanah; Ikbal Irawan; Muhammad Yusuf (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2026)
The Office of Cooperatives, Industry and Trade of Bima City functions to encourage and facilitate the formation and development of cooperatives in Bima City. This office also plays a role in increasing government support for cooperatives and ensuring that cooperatives operate well and provide benefits to the community. This type of research is associative, associative research is a formulation of a research problem that is intended to ask about the relationship between two or more variables. Work discipline has a significant effect on employee productivity at the Office of Cooperatives, Industry and Trade of Bima City. The Physical Work Environment does not have a significant effect on employee productivity at the Office of Cooperatives, Industry and Trade of Bima City. Work Discipline and the Physical Work Environment together have a significant effect on employee productivity at the Office of Cooperatives, Industry and Trade of Bima City